Simulation and experimental analysis of shell and tube heat exchanger for the drying system - Songchai Pankaew (2020)
© 2020 Institute of Physics Publishing. All rights reserved. In this research, heat transfer simulation is a part of the application of heat transfer from the biochar production process for the drying system. This research aimed to investigate the three-dimensional transient conditions of the simulation used to predict heat transfer of heat exchangers comparing with the experimental study. The working fluid used inside the tube was hot water with a mass flow rate of 10 LPM. The results obtained from the simulation and the experiment analysis were heat transfer from hot water to cold air through the heat exchangers. The temperatures of hot water inlet the heat exchanger were set as 50, 60, 70, and 80 °C, respectively. Air flowed through the heat exchangers was set as 1 m/s, 2 m/s, 3 m/s, 4 m/s, and 5 m/s, respectively. The coil pipe has the outsider diameter at 1.9 cm and four panels. It was set up on a box case with 100 cm of width and height and 45 cm of length. The results showed that when the water temperature increased from 50 °C to 80 °C and airflow speed through the heat exchangers of 3 m/s, the temperature difference of air through the heat exchangers increased from 3.2 °C, 4.7 °C, 5.20 °C and 6.2 °C respectively. On the other hand, when the airflow speed through the heat exchangers increased from 1 m/s to 2 m/s, 3 m/s, 4 m/s and 5 m/s respectively, the temperature difference of air through the heat exchangers decreased from 11.81 °C to 7.33 °C, 6.20 °C, 5.20 °C, and 5.05 °C respectively. The simulated heat transfer coefficient inside the region of heat exchangers was an agreement with the experimental data. The results indicated that the simulation could be attained in the system compared with the actual experimental analysis.